Strategies for combating corruption in Nigeria 1999-2015: effectiveness and challenges - Mikail, Ibrahim Kawuley (2018)
Corruption is a global impediment that affects all systems, organizations, institutions and nation states to meet the requisite for development. This study assesses the strategies for combating corruption in Nigeria 1999-2015, its effectiveness and challenges. In Nigeria, the governments made concerted efforts continuously to address corruption aiming at combating it to the barest minimal. Some commissions of inquiries, policies and programs (i.e. asset declaration, war against indiscipline, failed Bank Tribunal etc.) were put in place but the mission is unaccomplished. Thus, it motivates the government of fourth democratic republic to establish strategies to combat corruption in Nigerian public domain. This study employed qualitative method through in-depth interview for 12 informants and focus group discussion for 4 civil society organizations to the obtain data. While Nvivo version 10 was used for analysis. The study reveals that the fourth republic 1999-2015 has come up with different strategies (anti-graf institutions: Independent Corrupt Practices and other related offences Commission, Economic Financial and Crimes Commission and their components i.e. Bureau of Public Procurement, Nigerian Extractive Industries Transparency Initiatives and Technical Unit on Governance and Anti-Corruption Reform, Public Education and Programs etc.) in combating corruption. The strategies are relatively effective in combating corruption, because, they have some measures (investigation, prevention, education, prosecution and enforcement) that were taken in combating corruption. But, these strategies faced some challenges such as political interference, inadequate funding, lack of political will, immunity clause among others that hindered them to perform more effectively. Therefore, it is recommended that, political will and autonomy should be offered to all anti-graft institutions. The strategies shall be based on holistic approach in order to have collective response in combating the menace of corruption.